A 1997 Social Accounting Matrix (SAM) for Egypt: Aggregated Version - International Food Policy Research Institute (International Food Policy Research Institute, 2002)
The aggregated Egypt Social Accounting Matrix (SAM) was constructed for 1997 and has 14 sectors, 10 households, 4 factors, a government account and a rest-of-the-world account. There are 6 agricultural sectors, 4 manufacturing sectors, with the rest as service sectors. The agricultural sectors are: food crops, rice, other food crops, fruits and vegetables, cotton, and animal agriculture. The manufacturing sectors are: food processing, oil, textiles, and other manufacturing. The remaining service sectors are: electricity, construction, government sectors, and other services. The SAM differentiates between urban and rural households by quintiles, allowing welfare, inequality and poverty analysis. In addition to land and capital, the SAM distinguishes between agricultural and nonagricultural labor. For a description of the construction and use of this dataset, download the Trade and Macroeconomics Division Discussion Paper Number 78: (PDF 136K)